2023
DOI: 10.1113/ep091279
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cerebrovascular reactivity are modified by maturational stage and exercise training status during youth

Jack S. Talbot,
Dean R. Perkins,
Christine M. Tallon
et al.

Abstract: New Findings What is the central question of this study? Gonadal hormones modulate cerebrovascular function while insulin‐like growth factor 1 (IGF‐1) facilitates exercise‐mediated cerebral angiogenesis; puberty is a critical period of neurodevelopment alongside elevated gonadal hormone and IGF‐1 activity: but whether exercise training across puberty enhances cerebrovascular function is unkown. What is the main finding and its importance? Cerebral blood flow is elevated in endurance trained adolescent males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(213 reference statements)
0
6
0
Order By: Relevance
“…Coupled with the most recent findings from Talbot, Perkins, Tallon et al (2023), this suggests that exercise training in adolescents may be necessary to counteract the negative consequences of higher sedentary time on cerebral haemodynamics.…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…Coupled with the most recent findings from Talbot, Perkins, Tallon et al (2023), this suggests that exercise training in adolescents may be necessary to counteract the negative consequences of higher sedentary time on cerebral haemodynamics.…”
mentioning
confidence: 57%
“…In a separate study byTalbot et al, they reported that pre-PHV-trained children had a smaller increase in cerebral pulsatility of the posterior cerebral artery (PCA) during a visual stimulus, compared with untrained pre-PHV children.The interpretation is that trained children had better dampening function in the PCA, compared with untrained children. Thus, both findings from examining the cerebrovascular kinetics during a ʻstressʼ revealed exercise training adaptations in the pre-PHV cohort, prior to maturation.The faster ICA mean response time to hypercapnia in pre-PHV children(Talbot, Perkins, Tallon et al, 2023) is an interesting finding and brings to light questions for the field. For example, what is the physiological or clinical significance of a faster response to hypercapnia in children prior to reaching PHV or maturation?…”
mentioning
confidence: 87%
See 3 more Smart Citations